Sudan : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2013)
This paper focuses on Sudan's Interim Poverty Reduction Strategy Paper (I-PRPS). I-PRSP will support existing planning and budgeting instruments, including the 3-Year Salvation Economic Program (SEP) 2012-2014 and the 5-Year Development Plan (2012-2016), by strengthening the prioritization of actions and targeting poverty. The 3-Year SEP is an emergency plan to deal with the adjustment to new political and economic realities following the decision of the South to secede. I-PRSP will also help to fine tune the preparation and implementation of the SEP and a new 5-year Plan, and provide a foundation for the full PRSP.